Yield and water use efficiency of Barley fodder produced under hydroponic system in GCC countries using tertiary treated sewage effluents - Isam Kadim, Yahia Othman, Asadullah Al Ajmi, Ahmed Ali Salih, (Journal of Phytology, 2009)
In the Gulf Cooperation Council (GCC) Countries, where water is a major limitation in crop production, using alternative water resources such as tertiary treated sewage effluent (TTSE) is one way to produce crops, especially fodders which consume sizeable share of the limited irrigation water. Barley (Hordium vulgare L.) is a popular fodder in the region with good adaptability to wide range of climate and soil. A laboratory experiment was conducted during 2009 using complete randomized design with four replications in order to evaluate yield, water use efficiency (WUE) and quality of barley fodder irrigated with TTSE under hydroponic system. Barley seeds of a commercial grade with good viability (80-85%) were sterilized with 20% sodium hypochlorite solution to control fungal growth. Seeds were sown in stacked trays in a temperature controlled room. Trays were irrigated daily with either tap water (T1), or tap water mixed with TTSE at 20%, 40%, 60%, 80% (T2 to T5) and with TTSE only (T6). Plants were harvested 9 days after sowing. Plant height, green and dry fodder weight, the germination percentages and the amount of water used were recorded. Representative fresh green fodder samples from each treatment were oven-dried at 70oC for 48 hrs and analyzed. Crude protein, Crude fiber CF, acid detergent fiber (ADF), neutral detergent fiber (NDF) and lipid concentrations were determined. Results indicated that germination percent and yield of barley increased as the concentration of TTSE in irrigation water increased, however, the increase in WUE was not significant. Proximate chemical analyses indicated that there was no significant effect of treated sewage effluent on moisture, CF, NDF, ADF, or fat (ether extract) of the barley fodder. It was concluded that barley produced by TTSE maintained all its fodder quality and that it can be produced commercially for feeding livestock.